MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN BLENDED LEARNING DAN MOTIVASI BERPRESTASI SISWA - Ibrahim, Nurdin (Perspektif Ilmu Pendidikan, 2012)
The purpose of this research was to know the correlation between the blended learning or achievement motivation and learning achievement. Taking place in Open Junior Secondary School, Tanjung Priuk, affiliated to State Junior Secondary School, No. 55, Tanjung Priuk, the research was conducted as from May through June 2010. The research used survey method with statistical approach and the research focus are (a) the correlation between blended learning and learning achievement, (b) the correlation between achievement motivation and learning achievement, and (c) the correlation between both of blended learning and achievement motivation and learning achievement simultanously. The research proved (a) the positive correlation between blended learning and learning achievement, (b) the positive correlation between achievement motivation and learning avhievement, and (c) the positive correlation between both of blended learning and achievement motivation and learning achievement simultanously. In addition to the findings, the research also provided some suggestions related to instructional process